HUBUNGAN PLACE IDENTITY DENGAN IDENTITY OF COMMUNITY PADA CO-WORKING SPACE - Pristya Any Wulandari; Bambang Soemardiono; Muhammad Faqih (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: The continuous development of technology pursues the emergence of co-working, mainly in Surabaya with many enthusiasts, especially startups. Place identity is represented by Koridor Co-working Space. While identity of community by startups is dominated by Z and millennial. It is said that place and user can influence each other. In its application, co-working can accommodate many startups in one location. Co-working needs to express place identity and identity of community as user. Meanwhile startups, in their effort to express identity of community, need more space control. Only a little research has discussed place identity and identity of community that are specific to co-working. Thus this correlational research aims to identify the relationship of place identity and identity of community in co-working. Through post-positivism paradigm and the collected data through observation, documentation, archive and likert-scale questionnaire, data from 67 respondents were analyzed using descriptive statistical analysis. The results show that most startup members consider place identity of Koridor Co-working Space to be unique and very unique. From all aspects identity of community and place identity, two pairs of interconnected were found; education with shape and form of building and income with materials. Thus in this position, the hypothesis can be accepted.Keyword: Co-working space, identity of community, place identity Abstrak: Berkembangnya teknologi berkesinambungan dengan munculnya co-working space terutama di Kota Surabaya dengan banyak peminat, yaitu kelompok startup. Place identity diwakili oleh Koridor Co-working Space. Sementara identity of community diwakili oleh kelompok startup yang didominasi generasi Z dan Y. Diketahui bahwa tempat dan pengguna saling berhubungan. Dalam aplikasinya, co-working space dapat menampung banyak startup dalam satu lokasi. Co-working space perlu memunculkan place identity sekaligus identity of community sebagai penggunanya. Sementara kelompok startup dalam upaya memunculkan identity of community terhalang oleh kendali ruang yang terbatas. Belum banyak penelitian yang membahas tentang konsep place identity dan identity of community yang spesifik pada objek co-working space. Dengan begitu, penelitian correlational research ini memiliki tujuan untuk mengidentifikasi hubungan place identity dengan identity of community pada co-working space. Melalui paradigma post-positivism dan teknik pengumpulan data melalui observasi, dokumentasi, arsip dan kuesioner berskala likert, data dari 67 responden dianalisis menggunakan analisa statistik deskriptif. Hasilnya menunjukkan bahwa mayoritas anggota startup menilai place identity Koridor Co-working Space tergolong unik dan sangat unik. Selain itu, dari seluruh sub-variabel identity of community dan place identity yang dihubungan, ditemukan dua pasang yang terbukti berhubungan, yaitu pendidikan dengan bentuk bangunan serta pendapatan dengan material. Dengan demikian, pada posisi ini hipotesis dapat diterimaKata Kunci: Co-working space, identity of community, place identity